The equitable aging in health conceptual framework: international interventions infusing power and justice to address social isolation and loneliness among older adults - Perone, Angela K.; Urrutia-Pujana, Leixuri; Zhou, Leyi; Yaisikana, Mo’e; Mendez Campos, Barbara (Frontiers in Public Health, 2025)
IntroductionSocial isolation and loneliness among older adults have garnered significant international attention, particularly as structures and services have evolved during a global pandemic. A growing body of research underscores disparities in social isolation and loneliness among intersecting social (e.g., race, ethnicity, age, gender, sexual orientation, disability) and physical (e.g., rural/urban) locations. While empirical data about these global trends has increased, conceptual and theoretical frameworks are underdeveloped about disparities in social isolation and loneliness, especially from a global perspective. This article presents a novel equitable aging framework to help contextualize, understand, and explain how power influences disparities in social isolation and loneliness among older adults.Equitable aging in health conceptual frameworkEquitable aging builds on principles in critical gerontology, public health concepts of social and political determinants of health, international human rights, and intersectionality frameworks to present a new conceptual framework for researchers, policymakers, and practitioners. Equitable aging centers five domains of power (intrapersonal, interpersonal, disciplinary, structural, and cultural) as critical components (or hub) that drive six political and social determinants of health (economic stability, education access and quality, health care access and quality, neighborhood and built environment, social and community context, and laws and politics). The sixth determinant of health (laws and policies) incorporates international human rights (economic, social, cultural, civil, political rights). When justice is infused in these domains of power, political and social determinants of health can produce equitable aging outcomes. The Equitable Aging in Health Framework presents a new tool that incorporates justice and power to help understand and explain disparities in social isolation and loneliness and ultimately how to achieve equitable opportunities for social connections for older adults.DiscussionTo illustrate the utility of this conceptual framework, this article presents six case studies of interventions in China, Taiwan, Spain, Sweden, Mexico, and the United States that employ this framework to address social isolation and loneliness among diverse communities of older adults. These interventions propose new services, programs, and policies that infuse different paradigms of justice and address domains of power in various ways to build social connections and support for older adults.